The influence of adolescent red cross extracurriculars on students' discipline attitudes at SMA Negeri 1 Sekayu - Della Amelia; Sri Artati Waluyati (Universitas Muhammadiyah Enrekang, 2025)
This study aims to determine the influence of adolescent red cross extracurricular attitudes on the discipline attitude of students at SMA Negeri 1 Sekayu. This study uses a quantitative approach with a descriptive statistical method. This study has a population of 50 people using the probability sampling technique with the Proportionate Stratified Random Sampling method with an error rate of 5%, the number of samples in this study is 45 people. The data collection technique in the study showed that there was an influence on the extracurricular red cross of adolescents on disciplinary attitudes at SMA Negeri 1 Sekayu. This is evidenced by looking at the results of a simple regression test, namely the results obtained by Constant (α) are 1.352 adolescent red cross extracurriculars while the value of discipline attitude (b) is 0.613. Based on the results of the study, it was concluded that there was an influence of adolescent red cross extracurricular attitudes on the discipline attitude of students at SMA Negeri 1 Sekayu.